The evolution of academic databases and their different paradigms - Ortega, José-Luis (Anuario ThinkEPI, 2024)
The aim of this entry is to take a tour through the different types of scholarly databases, and how they have been understood throughout the time according to their historical and technological contexts. We will review the origins of the first citation indexes, the appearance of academic search engines with the advent of the Web and conclude with the new databases based on third parties. In this way, we intend to show the current status of these different approaches and how they can respond to the current challenges of digitization and open science.